A radar analysis equatorial precipitating Clouds at Thumba (MAUSAM, 1970)
The precipitating cloud echoes detected by a 10cm radar (S-band) at Thumba (Lat, 08°32'N, Longo 'n in storms 76°52' E) have been analysed to find out the main characteristics of the equatorial cloud system-horizontal of and vertical dimensions, extent and nature of line formation, distance between individual cloud cells and line echoes, structure development and movement.         Assuming the precipitating system to be circular and moving with uniform speed, the horizontal dimension of a cloud system which passed through a close triangular network of meteorological stations in Trivandrum was calculated and compared with the nearest available radar observations. The cloud dimension and movement were and it com- found to be in good agreement with radar observations.